2022
DOI: 10.3390/ijerph19084835
|View full text |Cite
|
Sign up to set email alerts
|

Medication Self-Management in Hospitalised Patients with Schizophrenia or Bipolar Disorder: The Perceptions of Patients and Healthcare Providers

Abstract: Aim(s): The aim of the study was to explore perspectives of hospitalised patients with schizophrenia or a bipolar disorder and their healthcare providers on medication self-management. Methods: In a qualitative descriptive design, semi-structured interviews were used. Forty-nine interviews were completed (nurses n = 18; psychiatrists n = 3; hospital pharmacists n = 2; patients n = 26). Data analysis was iterative using an inductive and thematic approach. Results: From the thematic analysis of the interviews, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 31 publications
6
9
0
Order By: Relevance
“…Nurses were more willing than psychiatrists. These findings were in line with those of previous qualitative research (Loots et al, 2022). Psychiatrists were more worried about the risks associated with MSM in the hospital, such as the difficulty in assessing the patients, the social aspect (e.g., peer pressure and medication mix‐ups,…), and medication errors (Loots et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Nurses were more willing than psychiatrists. These findings were in line with those of previous qualitative research (Loots et al, 2022). Psychiatrists were more worried about the risks associated with MSM in the hospital, such as the difficulty in assessing the patients, the social aspect (e.g., peer pressure and medication mix‐ups,…), and medication errors (Loots et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…These findings were in line with those of previous qualitative research (Loots et al, 2022). Psychiatrists were more worried about the risks associated with MSM in the hospital, such as the difficulty in assessing the patients, the social aspect (e.g., peer pressure and medication mix‐ups,…), and medication errors (Loots et al, 2022). Besides the insight gained into the willingness of healthcare providers toward MSM, the results indicated that some implementation aspects are lacking.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study highlights the importance given by patients to take part in the decision about the treatment they should receive, especially in long-term follow-up (chronic phase). Others clinical studies have demonstrated the effectiveness of the decision shared by people who have BD [36,37] and other chronic psychotic disorders such as schizophrenia, showing effectiveness and improvement in the quality of decisions based on the increase in knowledge and participation, and observing a greater congruency with the values and preferences of the participant, as well as an increase in user satisfaction [37][38][39]. This shared decision making should be viewed as a dynamic process, where information is shared and reflected, and support is provided.…”
Section: Discussionmentioning
confidence: 99%